EXPLORING THE IMPACT OF COVID-19 PANDEMIC ON THE MENTAL HEALTH OF NGO STAFF IN BANGLADESH, FOCUSING ON STRESS AND COPING - Shajeda Begum; Rubayat Kabir; Md Sanaul Haque Mondal
Non-governmental organizations (NGOs) played a pivotal role during the COVID-19 pandemic by being at the forefront of responding to the global upsurge in humanitarian needs. The purpose of this study is to find out the factors associated with stress among NGO staff due to the COVID-19 pandemic. This study employed qualitative phenomenological research design and the data were collected using in-depth interviews from fifteen NGO staff. Thematic analysis technique was adopted for the data analysis. This study identified numerous stressors, including challenges of work-life balance, social isolation, and access to treatment facilities. Seven out of fifteen respondents stated that the extended hours they worked during COVID-19 had an impact on their ability to maintain a healthy work-life balance. The majority of the respondents felt anxious about getting access to treatment facilities during the COVID-19 pandemic due to higher treatment costs and limited treatment facilities. The respondents used a variety of coping mechanisms to deal with these stressors, including communicating and spending time with friends and family members, and engaging in fun activities such as watching movies, crafting, gardening, and reading. NGO staff’s daily lives and their mental health were severely impacted by the COVID-19 pandemic. This study recommends the need to assess the stress of NGO staff so that early measures can be taken by concerned NGO agencies, such as employers, to take proactive measures to mitigate their stress during pandemics or other emergencies.